Emphasizing Growth and Thermal Studies of Doped and Pure Crystals of L-Argininium Dinitrate - Preema C. Thomas; P. Sagayaraj (New Insights into Physical Science Vol. 12, 2021)
Single crystals of pure and Cu2+ doped semiorganic L-argininium dinitrate (LADN) crystals were grown by slow solvent evaporation technique, with the vision to improve the physicochemical properties of the sample. Single crystal XRD studies of both pure and doped samples were carried out. The thermal (DTA, TGA and DSC) studies were carried out and the results are compared.The NLO studies show that doping has improved the NLO efficiency of pure LADN crystals. From thermal studies it is observed that the presence of metal dopant (Cu2+) increases the decomposition temperature of LADN.